LEXICAL ISSUES IN TRANSLATION THEORY AND COMMON WAYS OF OVERCOMING THEM - Khaydarova , Laylo Khamroyevna; Mustafayeva , Mokhiniso Oybekovna (Innovative Development in Educational Activities, 2023)
This article will discuss common lexical problems which give a rise during translation study. As the translation field incorporated into the curriculum of students, its difficulties cannot be avoided and thus should be suppressed with several lexical transformations, which will be described in the article as well